Pengaruh Tata Kelola Perusahaan Dan Modal Intelektual Terhadap Financial Distress - Almira Raina, Andi Tendri; Prastiwi, Arum (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to examine the effect of corporate governance and intellectual capital on financial distress utilizing the Zmijewski method. The population includes 609 non-financial companies listed on the Indonesia Stock Exchange between 2018 and 2021, from which the samples of 120 observable data are selected through purposive sampling. This study involves secondary data of the companies’ annual reports collected from their official websites and that of IDX (www.idx.co.id) and analyzed by multiple linear regression utilizing IBM SPSS Statistics 26. This study finds that corporate governance does not affect financial distress, and intellectual capital has a negative effect on financial distress; implying that corporate governance does not whatsoever contribute to financial distress, and higher intellectual capital, represented by Value-Added Intellectual Capital (VAIC), can minimize the likelihood of financial distress.